THE EFFECTIVENESS OF VITAMIN C AND E ADDITION IN VARIOUS DILUENTS OF BRAHMAN CATTLE SPERMATOZOA AFTER FREEZING - Suharyati, Sri; Hartono, Madi; Siswanto, Siswanto; Nur Wahid, Agus; Rangga Saputra, Hanip; Nilam Sari, Fatma (Jurnal Kedokteran Hewan, 2024)
This research aimed to determine the quality of Brahman cattle spermatozoa after freezing in various diluent ingredients (Egg Yolk Citrate, Egg Yolk Tris, Skim Milk) which added vitamin C and vitamin E. The research was carried out using 4 treatments with 3 different diluent ingredients, each of which was Vitamins C and E are added to each diluent ingredient at a dose adjusted to the type of diluent agent. The treatment given is P0: Diluent without Vitamin C and E; P1: Diluent + Vitamin C; P2: Diluent + Vitamin E; and P3: Diluent + Vitamin C and Vitamin E. Research data were analyzed using analysis of variance and followed by Duncan's test at the 5% and/or 1% level for different variables. The results showed that the addition of vitamin C and vitamin E had a significant effect (P0.05) on motility and viability in the egg yolk tris diluent and egg yolk citrate but had no significant effect (P0.05) in the skim milk diluent. The use of different diluents had no significant effect (P0.05) on motility, viability, and abnormalities. This research concludes that Vitamin C added to the diluent tris egg yolk, egg yolk citrate, and skim milk showed higher average motility, percentage of live spermatozoa, and abnormalities of post-freezing Brahman cow spermatozoa.